A convex optimization-based traffic matrix estimation approach in IP-over-WDM backbone networks. (April 2015) - Nie, Laisen; Jiang, Dingde; Guo, Lei
Abstract: With the rapid development of an IP-over-WDM network, it has become a complex and heterogeneous network. In such a case, network management is a crucial role for promoting the efficiency of the IP-over-WDM network. A traffic matrix, which provides an intrinsic and flow-level view of our networks, is required to perform network management tasks such as traffic engineering function. Unfortunately, limited by current technologies, it is significantly difficult to acquire the exact traffic matrix. Motivated by this issue, in this paper, we investigate the traffic matrix estimation problem in an IP-over-WDM backbone network. We develop a simple algorithm based on the network tomography method. In order to deal with the ill-posed property of the traditional network tomography method, we refer to the origin–destination traffic demands of the optical layer in our method. We first study the relationship between the traffic matrix and optical layer traffic demands. Thereby, we take advantage of the relationship between them to construct a linear system. Combining with the traditional network tomography model, we propose a convex and unconstrained optimization model for estimating the traffic matrix. Finally, we also provide numerical results to validate the performance of the proposed method in this literature.